K
Khách

Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.

16 tháng 9 2024

 * Công thức: a² - b² = (a + b)(a - b)
Áp dụng:
 * 4x² - 9
 * = (2x)² - 3²
 * = (2x + 3)(2x - 3)

20 tháng 1 2017

b) 4x2 – 9 + (2x + 3)2

= (4x2 - 9) + (2x + 3)2

= (2x + 3)(2x - 3) + (2x + 3)2

= (2x + 3)(2x - 3 + 2x + 3)

= 4x(2x + 3)

12 tháng 12 2021

a/ \(4x^2-9\)

\(=\left(2x-3\right)\left(2x+3\right)\)

b/ \(3x\left(3x-2\right)+1\)

\(=9x^2-6x+1\)

\(=\left(3x-1\right)^2\)

12 tháng 12 2021

\(a,=\left(2x-3\right)\left(2x+3\right)\)

\(b,=9x^2-6x+1=\left(3x-1\right)^2\)

29 tháng 10 2021

a: \(7x-14y=7\left(x-2y\right)\)

b: \(4x^2-4x+1=\left(2x-1\right)^2\)

11 tháng 12 2023

a) $4x^2+4x+1$

$=(2x)^2+2\cdot2x\cdot1+1^2$

$=(2x+1)^2$

b) $x^2+6x-y^2+9$

$=(x^2+6x+9)-y^2$

$=(x^2+2\cdot x\cdot3+3^2)-y^2$

$=(x+3)^2-y^2$

$=(x+3-y)(x+3+y)$

$\text{#}Toru$

11 tháng 12 2023

a: \(4x^2+4x+1\)

\(=\left(2x\right)^2+2\cdot2x\cdot1+1^2\)

\(=\left(2x+1\right)^2\)

b: \(x^2+6x-y^2+9\)

\(=\left(x^2+6x+9\right)-y^2\)

\(=\left(x+3\right)^2-y^2\)

\(=\left(x+3+y\right)\left(x+3-y\right)\)

\(A=x^2-y^2+7x+7y\)

\(=\left(x-y\right)\left(x+y\right)+7\left(x+y\right)\)

\(=\left(x+y\right)\left(x-y+7\right)\)

\(B=4x^3-4x^2+x\)

\(=x\left(4x^2-4x+1\right)\)

\(=x\left(2x-1\right)^2\)

\(C=x^2-6xy+9y^2-9\)

\(=\left(x-3y\right)^2-9\)

\(=\left(x-3y-3\right)\left(x-3y+3\right)\)

26 tháng 8 2021

A=\(x^2+7x+7y-y^2=\left(x^2-y^2\right)+\left(7x+7y\right)=\left(x-y\right)\left(x+y\right)+7\left(x+y\right)=\left(x+y\right)\left(x-y+7\right)\)

B=\(4x^3-4x^2+x=x\left(4x^2-4x+1\right)=x\left(2x-1\right)^2\)

C=\(x^2+9y^2-9-6xy=\left(x^2-6xy+9y^2\right)-9=\left(x-3y\right)^2-3^2=\left(x-3y-3\right)\left(x-3y+3\right)\)

13 tháng 1 2019

3 tháng 9 2021

a) \(x^2-9+2\left(x+3\right)=\left(x-3\right)\left(x+3\right)+2\left(x+3\right)=\left(x+3\right)\left(x-3+2\right)=\left(x+3\right)\left(x-1\right)\)

b) \(x^2-10x+25-3\left(x-5\right)=\left(x-5\right)^2-3\left(x-5\right)=\left(x-5\right)\left(x-5-3\right)=\left(x-5\right)\left(x-8\right)\)

c) \(x^3-4x^2+3x=x\left(x^2-4x+3\right)=x\left(x-1\right)\left(x-3\right)\)

a: \(=x\left(x^2+4x+4-z^2\right)\)

\(=x\left(x+2-z\right)\left(x+2+z\right)\)

9 tháng 11 2021

z còn câu b

14 tháng 4 2017